1968
DOI: 10.1039/j39680000452
|View full text |Cite
|
Sign up to set email alerts
|

The biosynthesis of pteridines. Part V. The synthesis of riboflavin from pteridine precursors

Abstract: The synthesis and reactions of various 8-substituted lumazine derivatives are described. In particular, it is shown that these compounds readily undergo hydration, and that the resulting carbinol-amines can take part in reactions which involve ring-opening in the pyrazine ring. These studies are extended to demonstrate a new chemical synthesis of riboflavin and related isoalloxazines from 8-substituted pteridine derivatives. A possible mechanism for this reaction, which is analogous to that involved in the bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Appropriate conditions for the nonenzymatic conversion of 2 molecules of 6,7-dimethyl-8-ribityllumazine to RF and 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione are boiling water solutions at acidic or neutral pH (28,29,380).…”
Section: Riboflavin Synthasementioning
confidence: 99%
“…Appropriate conditions for the nonenzymatic conversion of 2 molecules of 6,7-dimethyl-8-ribityllumazine to RF and 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione are boiling water solutions at acidic or neutral pH (28,29,380).…”
Section: Riboflavin Synthasementioning
confidence: 99%
“…Their elegant work has been reviewed repeatedly (2,23,24). Wood, Plaut, and their coworkers have found that the dismutation of the lumazine that leads to the formation of riboflavin can also proceed nonenzymatically in boiling aqueous solution over a wide pH range (8,22,27).The sequences of riboflavin synthases from several eubacterial species and from yeast have been reported (10,13,14,(18)(19)(20) and are characterized by sequence homology between the N-terminal and C-terminal halves, suggesting that the peptides form two homologous folding domains (29). Riboflavin synthases of Bacillus subtilis and Escherichia coli are trimers of identical subunits.…”
mentioning
confidence: 99%
“…Thus, riboflavin is obtained on boiling of neutral or acidic aqueous solutions of 6,7-dimethyl-8-ribityllumazine (2,3). The enzyme-catalyzed and the uncatalyzed reactions proceed with identical regiochemistry involving a head-to-tail arrangement of the two 4-carbon moieties from which the xylene ring of riboflavin is assembled (4)(5)(6).…”
mentioning
confidence: 99%
“…The exomethylene type lumazine anion (1a) was proposed to attack the adduct of a second substrate molecule and a nucleophile (2) resulting in the formation of a lumazine dimer (3) as an initial reaction step ( Fig. 1; refs.…”
mentioning
confidence: 99%